Ketamine for Refractory Chronic Migraine: An Observational Pilot Study and Metabolite Analysis. (9th July 2021) - Schwenk, Eric S.; Torjman, Marc C.; Moaddel, Ruin; Lovett, Jacqueline; Katz, Daniel; Denk, William; Lauritsen, Clinton; Silberstein, Stephen D.; Wainer, Irving W.
Abstract: Patients with refractory chronic migraine have substantial disability and have failed many acute and preventive medications. When aggressive intravenous therapy is indicated, both lidocaine and (R, S)‐ketamine infusions have been used successfully to provide relief. Retrospective studies have shown that both agents may be associated with short‐term analgesia. In this prospective, observational pilot study of 6 patients, we compared the effects of lidocaine and (R, S)‐ketamine infusions and performed metabolite analyses of (R, S)‐ketamine to determine its metabolic profile in this population. One of (R, S)‐ketamine's metabolites, (2R, 6R)‐hydroxynorketamine, has been shown in animal studies to reduce pain, but human studies in patients undergoing continuous (R, S)‐ketamine infusions for migraine are lacking. All 6 patients tolerated both infusions well with mild adverse effects. The baseline mean pain rating (0‐10 numeric rating scale) decreased from 7.5 ± 2.2 to 4.7 ± 2.8 by end of lidocaine treatment ( P ≤ . 05 ) but increased to 7.0 ± 1.4 by the postdischarge visit at 4 weeks ( P > .05 vs baseline). The baseline mean pain rating prior to ketamine treatment was 7.4 ± 1.4, which decreased to 3.7 ± 2.3 by the end of the hospitalization ( P ≤ . 05 ) but increased to 7.2 ± 1.7 by the postdischarge visit at 6 weeks ( P > .05 vs baseline). For the primary outcome the change in pain from baseline to end of treatment was greater for ketamine than lidocaine (–3.7 vs –2.8; P ≤ . 05 ), but this has minimal clinical significance. Ketamine metabolite analysis revealed that (2R, 6R)‐hydroxynorketamine was the predominant metabolite during most of the infusion, consistent with previous studies.